Hydrogen production via simultaneous methane reforming and water splitting processes using membrane reactor - Sureena, Abdullah (2014)
The main objective of this study is to investigate on the ability of a perovskite-based membrane reactor to produce hydrogen via simultaneous reforming and water splitting processes. Being able to perform such processes will confirm on the ability of the membrane system in performing an autothermal production of hydrogen. Initial experiments were conducted to evaluate the ability of two different types of hollow fibre membrane namely Lao.6Sro.4Co0.2Feo.8O3- (LSCF6428) and BaosSro.sCoo.8Feo.203- (BSCF5582) in permeating oxygen in three different inlet configurations. All of the experiments were conducted at 9000C. The LSCF6428 membrane gives lower oxygen permeation rate comparing to BSCF5582 when inert gas argon was used as the sweep gas on the shell side of the membrane. The oxygen permeation rate.--into the shell side of LSCF6428 membrane reactor was at 0.24pmolO.s 1 whereas for BSCF5582 was at 1.50iimol O.s 1. The trend is similar when the shell sides were fed with 5% methane and the lumen sides were fed with 10% oxygen. In these experiments, both membranes were stable enough to perform oxygen permeation up to more than 100 hours of operation. BSCF5582 membrane however shows instability in performing oxygen permeation when the lumen side was fed with 4% water and shell side was fed with 5% methane. BSCF5S82 membrane was only able to perform oxygen permeation for less than two hours before showing substantial amount of leaks upon breaking. In contrast, the LSCF6428 membrane shows good stability in the same condition with the shell side oxygen permeation rate of 0.04±0.01timolO.s 1. The experiment operating time lasted for more than 90 hours. Based on its stability in performing oxygen permeation in the combination of highly reducing and highly oxidising environment, the LSCF6428 membranes were chosen to perform the simultaneous methane reforming and water splitting process in a multiple-membrane based reactor. The results obtained from this experiment proved that simultaneous methane reforming and water splitting can be achieved using a membrane reactor.